Indonesia-Malaysia cultural network of Minangkabau diaspora: a preliminary finding - Mundayat, Aris Arif (Pusat Penyelidikan Bitara Melayu, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2016)
This article assesses social and cultural network between Indonesia and Malaysia through the Minangkabau diaspora in Malaysia within the context of cultural change. Qualitative method used in this study includes the observation of the Minangkabau cultural changes, then the documentary studies to explore the historical information regarding Minangkabau diaspora in Malaysia and its impact to the matrilineal kinship system. The unstructured interview also used to interview the second, third or fourth generation of Minangkabau diaspora, and the new migrant Minangkabau. This paper introduces the concept of “patrilinealization” and “nuclear-familization” that influence to the cultural change among the third or fourth generation of Minangkabau diaspora. These factors have made them uprooted from their cultural roots; however, some are practicing the hybrid culture. Although this paper shows about the social and cultural changes of Minangkabau in Malaysia, the potency of social and cultural networks remains potential as they still utilizing their network for cultural and economic purposes. The network between the diasporic communities in Malaysia has a positive potency to develop cultural community network in the region.